2014
DOI: 10.1002/ejic.201402920
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamate‐Functionalized Cage Silsesquioxanes as Photoreactive Nanobuilding Blocks

Abstract: Starting from potassium cinnamate, photoreactive mono-, octa-, and deca(propyl cinnamate)-functionalized cage silsesquioxanes were synthesized by simple nucleophilic substitution reactions with chloropropyl-substituted octasilsesquioxanes. Among them, octa(propyl cinnamate)silses-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The higher thermal stability of OazoSQ over MazoSQ might imply the formation of a stable network through self‐polymerization of OazoSQ during the heating process 32. 41, 42 The TGA analysis was also run in air at 10 °C min −1 . Whereas the ceramic yield of OazoSQ was closer to the expected yield of SiO 2, the residual mass of MazoSQ was less than the theoretical value.…”
Section: Resultsmentioning
confidence: 99%
“…The higher thermal stability of OazoSQ over MazoSQ might imply the formation of a stable network through self‐polymerization of OazoSQ during the heating process 32. 41, 42 The TGA analysis was also run in air at 10 °C min −1 . Whereas the ceramic yield of OazoSQ was closer to the expected yield of SiO 2, the residual mass of MazoSQ was less than the theoretical value.…”
Section: Resultsmentioning
confidence: 99%
“…On/off fluorescent switching and photostabilization via reversible cis‐trans isomerization have been also reported . Photo‐induced polymerization as well as cis‐trans photoisomerization studies in the presence of silsesquioxane nano‐cages have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of functional groups, such as olefins, acrylates, phenols, fluoroalkyls, halides, amines, sulfhydryls, azides, nitriles, phosphines, carbazoles, imidazolium salts, azobenzenes, cinnamates, etc., can be used for this purpose [4,7]. Some examples of current applications of these functionalized POSS are: phenyl functionalized POSS are promising as gas separation membranes or as surface coatings for electronic or optical devices owing to their excellent thermal stability and electrical insulation [16,17]; vinyl-functionalized POSS can be grafted to or copolymerized with polymers because of the unsaturated groups on the surface [18]; amino-functionalized POSS hybrid composites show high reactivity and oxidation resistance [19,20]; and mercaptofunctionalized POSS can adsorb proteins or metal ions [21,22]. The functionalization of POSS is of great significance for the subsequent design and synthesis of intermediates and materials.…”
Section: Engineering Possmentioning
confidence: 99%